Teachers training in Normal Schools of México. XX Century - Navarrete-Cazales, Zaira (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
This article presents a historical overview on the state of the normal schools of Mexico. The normal school has been the main institution responsible for the training of teachers for basic school level (preschool, primary, secondary) Training approaches circulating in this institution have gone hand in hand with national education policies while the Federal Government  through the Ministry of Public Education is responsible for the training of teachers in normal schools, therefore, the study (of both: approaches and policies) is essential to understand the course of normal schools during the twentieth century.Through a historical-documented review we account for its main stages: permanence, creation, nominal changes, prevalent theoretical trends, political moments that define it, inter alia. We conclude that with normal schools starts the teacher training, although in 1982, normal schools acquired the status of higher education institutions, its fate remains tied to basic education, by the weight of both, history and law.